Internet of Things (IoT) for Energy Efficiency in Tourism- Related Industry. - Komsary, Kasih Cakaputra; Ernawati, Tati; Hodijah, Ade; Wardiana, Dian (Pertanika Journal of Social Sciences & Humanities, 2020)
Internet of Things (IoT) has been considered as an alternative solution to the problem of energy efficiency in the tourism industry. IoT can be applied in supporting an environmentally friendly tourism industry. This study aims to see the possibilities of implementing IoT in the tourism SMEs (small-medium enterprises) by designing a simple prototype of a light controlling device as a solution to reduce energy consumption in the tourism-related industry. The prototype was designed by collaborating IoT, mobile devices and sensors in an electronic device (microcontroller Atmega 328P-PU) for lighting control. Furthermore, the switching device can be operated using an Android-based smartphone. The black box test examining the functionality of an application without peering into its internal structures or workings was carried out in the system, both server and client. The test results indicate that the device is functional, and wider use of IoT in the tourism industry in Indonesia is possible with a breakthrough in exploring the use of information technology.